Accommodation processes in irradiated steel 12Х18Н10Т during plastic deformation in the temperature range of “dry” SNF storage - Aldabergenova, T.; Akayev, S.; А.; Larionov А.; Dikova, L. (Recent Contributions to Physics, 2024)
This paper presents a detailed study of the fracture surfaces of 12Kh18N10T austenitic stainless-steel specimens subjected to short-term mechanical testing at various temperatures: 24°C, 350°C, and 450°C. The specimens for the study were fabricated from spent nuclear fuel of the BN-350 reactor. The research was conducted within the framework of a multi-level approach to physical mesomechanics, which allowed for a deeper understanding of the complex processes occurring in the material under different temperature regimes. In particular, a thorough analysis of the changes in the steel’s plasticity with increasing test temperature was carried out, revealing a significant dependence of this parameter on the conditions of deformation localization. It was shown that the reduction in plasticity with increasing test temperature is associated with a quasi-uniform distribution of stresses in the zones of deformation localization. These zones of local stress concentration were caused by processes that led to an increase in the material’s porosity, which, in turn, was due to accommodation processes of the rotational type. Thus, the study demonstrated the importance of considering local changes in the material’s structure, which can significantly affect its mechanical properties under varying operating conditions. The obtained results may contribute to a deeper understanding of the processes occurring in austenitic steels used in extreme conditions and aid in the development of more reliable materials for use in nuclear and other high-stress systems.